Psychological couple-oriented interventions for patients with heart disease and their partners: a scoping review and guidelines for future interventions - Rapelli, Giada; Giusti, Emanuele Maria; Tarquinio, Claudia; Varallo, Giorgia; Franceschini, Christian; Musetti, Alessandro; Gorini, Alessandra; Castelnuovo, Gianluca; Pietrabissa, Giada (Frontiers in Psychology, 2023)
Objective: This scoping review aims to provide an accessible summary of available evidence on the efficacy of psychological couple-based interventions among patients with heart disease and their partners focusing on specific aspects and strategies by assessing different emotional and physical cardiac-related outcome measures. Methods: A literature search was performed in PubMed, Scopus, Medline, PsycINFO, and Web of Science databases using the keywords “heart diseases” and “couple-based intervention”. A literature search using systematic methods was applied. Data were extracted to address the review aims and were presented as a narrative synthesis. Results: The database search produced 11 studies. Psychological couple-based interventions varied in terms of the type of intervention, personnel, format (group or individual, phone or in person), number of sessions, and duration. Most of the contributions also lacked adequate details on the training of professionals, the contents of the interventions, and the theoretical models on which they were based. Finally, although partners were involved in all the treatment, in most studies, the psychological strategies and outcomes were focused on the patient. Conclusions: The variability of the psychological couple-based interventions of included studies represents a challenge in summarizing the existing literature. Regarding their impact, psychological interventions for patients with cardiovascular disease and their partners were found to moderately improve patients’ and partners’ outcomes.